Chemical synthesis of the thymidylate synthase gene. - Climie, S (1990)
A 978-base-pair gene that encodes thymidylate synthase (TS; 5,10-methylenetetrahydrofolate:dUMP C-methyltransferase, EC 2.1.1.45) from Lactobacillus casei has been synthesized and inserted into Escherichia coli expression vectors. The DNA sequence contains 35 unique restriction sites that are located an average of 28 base pairs apart throughout the entire length of the gene. A ribosome binding site was included 9 base pairs upstream from the translation start site and codon usage was adjusted to ensure efficient translation in E. coli. The TS gene is flanked by unique EcoRI and HindIII restriction sites that render the gene portable to any of several E. coli expression vectors. Catalytically active TS encoded by the synthetic gene is expressed in large amounts (10-20% of the soluble protein) and is indistinguishable from that isolated from L. casei. The utility of the synthetic gene for mutagenesis is demonstrated by a single experiment in which His-199 was replaced with 14 different amino acids. Analysis of the mutants by genetic complementation indicates that TS can tolerate a number of amino acid substitutions at that position and shows that His-199 is not strictly required for catalytic activity.